Analysis of the Influence of Technical Expertise, Market Orientation, Social Capital, and Innovation on the Performance of Micro and Small Businesses in the Technology Sector - Manafe, Mesri Welhelmina Nisriani; Rizani, Ahmad; Purnawati, Elisa (IJBLE Scientific Publications Community Inc., 2024)
In today's rapidly evolving technology sector, the performance and sustainability of micro and small businesses hinge upon various factors, including technical expertise, market orientation, social capital, and innovation. Understanding the intricate interplay among these variables is crucial for devising effective strategies that foster growth and competitiveness within the industry. This research aims to explore the influence of technical expertise, market orientation, social capital, and innovation on the performance of micro and small businesses operating in the technology sector. Through empirical investigation and data analysis using Partial Least Squares Structural Equation Modeling (PLS SEM) with a sample of 100 businesses, this study sheds light on the relationships among these key factors and their implications for business success.